Controlling the level of water in a tank using Arduino Uno - Alkhashman, Mohammad Rajab; Kabbara, Khalid (My University, 2021)
Controlling liquid levels in a given medium can be complex and challenging to some extent. This project demonstrates how a system built from Arduino Uno, motor pump, water level sensor, water tank and a motor shield can automatically control water level in a tank despite the presence of disturbances. The microcontroller on the Arduino Uno is programmed using the Arduino Integrated Development Environment. The program controls the PWM of the motor pump, the PID:s parameters and the sensor. A graphical user interface is also created using Java as a programming language in the development environment Processing 3.3D printed tools are designed and printed for the assembly of the materials. The results showed a fully functional water regulating system that is capable of controlling the level of water in a tank depending on a chosen setpoint. A graphical user interface is successfully created using Java as the programming language in the development environment Processing 3.
Keywords: Control system; Arduino Uno; sensor; graphical user interface